Respuesta :

Answer:

u = [tex]\frac{vf}{2v-f}[/tex]

Step-by-step explanation:

[tex]\frac{1}{v}[/tex] + [tex]\frac{1}{u}[/tex] = [tex]\frac{2}{f}[/tex]

multiply through by uvf to clear the fractions

uf + vf = 2uv ( subtract 2uv from both sides )

uf - 2uv + vf = 0 ( subtract vf from both sides )

uf - 2uv = - vf ← factor out u from each term on the left side

u(f - 2v) = - vf ← divide both sides by (f - 2v)

u = [tex]\frac{-vf}{f-2v}[/tex] ( multiply numerator/ denominator by - 1 )

u = [tex]\frac{vf}{2v-f}[/tex]

ACCESS MORE